Transforming leaders the Sandler way - Arch, Dave (Gildan Audio, 2019)
You can't transform a team or an organization until you've transformed yourself. That's the idea behind Dave Arch's Transforming Leaders The Sandler Way, which offers a user-friendly guide to the fifty-two critical leadership lessons that support great careers and great teams.